VOCALIZATION OF THE CROCODILE SKINK, TRIBOLONOTUS GRACILIS (DE ROOY, 1909), AND EVIDENCE OF PARENTAL CARE. - Hartdegen, Ruston W.; Russell, Matthew J.; Young, Bruce (Contemporary Herpetology, 2001)
The crocodile or spiny skinks, Tribolonotus, comprise eight secretive semi-fossorial lizards, which are generally found under vegetation in the immediate vicinity of water (Greer and Parker, 1968; O’Shea, 1991, 1994; Rogner, 1997). Tribolonotus gracilis (Figure 1) and Tribolonotus novaeguineae are restricted to New Guinea, while the remaining six species range throughout Indonesia, Manus, New Britain, Bougainville, and the Solomon Islands (McCoy, 1980; O’Shea, 1991, 1994). Because scant life history information is available for the genus Tribolonotus, the purpose of the present contribution is to document the vocalization and parental care of T. gracilis.